Effect of high fructose administration on histopathology of kidney, heart and aorta of rats - Saleh, Rasha; Merghani, Basma H.; Awadin, Walaa (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was conducted to assess the hazardous effects of high fructose administration on kidney, heart and aorta in rats. Materials and methods: Twenty adult healthy male albino rats weighing about 200-220 gm each were used in this study. The rats were divided into 2 duplicate groups; control group and fructose group. Fructose was administered to rats in fresh drinking water daily for 8 weeks (the whole experimental period). Serum urea, creatinine and sodium concentration were determined by using ready-made kits. Spectrophotometric and colorimetric methods were also used for the detection of other serum components. Histopathological examination of the tissues was done by staining with H&E, PAS and Masson trichrome stains. Results: Nephropathy was achieved in fructose group after one month as indicated by biochemical assay. Pathological observation showed that high fructose administration decreased size of cardio-myocytes, increased cardiac interstitial fibrosis score and aortic wall thickness. In kidneys, high fructose administration decreased glomerular tuft area and corpuscular area, increased percentage in the rats affected with interstitial renal fibrosis score 1 and percentage of rats had glomerular sclerosis score 2. Conclusion: High fructose in diet should be avoided because it can damage kidney, heart and aorta in rats. http://doi.org/10.5455/javar.2017.d193